2011
DOI: 10.1111/j.1365-2427.2011.02618.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory in omnivorous fishes: effect of plant secondary metabolites and prey stoichiometry

Abstract: 1. Many animals that consume freshwater macrophytes are omnivorous (i.e., they include both plant and animal matter in their diet). For invertebrate omnivorous consumers, selection of macrophyte species depends partly on the presence of secondary metabolites in plants, plant carbon ⁄ nutrient balances and ⁄ or physical structure of plants. However, little is known about the mechanisms influencing consumption of macrophytes in aquatic vertebrates. 2. For two fish species, the omnivorous rudd (Scardinius erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 46 publications
(54 reference statements)
8
69
0
Order By: Relevance
“…This was particularly due to the increased concentrations of N and P, whereas the C concentration was somewhat lower in the animal prey compared to the plant material, but the difference was not as large as in N or P. Consumers are predicted to preferentially eat food with a composition similar to their own bodies (Elser et al, 2000). A similar result was found in an experiment with fish where rudd and grass carp consistently preferred animal prey over plant food, both in short-term feeding trials at 18°C and in 10-week pond experiments with water temperatures varying from 16 to 24°C (Dorenbosch & Bakker, 2011. Even though the omnivores showed a consistent strong preference for animal prey, they did consume plant material in the choice trial at all temperatures where both food types were presented ad libitum.…”
Section: Discussionsupporting
confidence: 68%
“…This was particularly due to the increased concentrations of N and P, whereas the C concentration was somewhat lower in the animal prey compared to the plant material, but the difference was not as large as in N or P. Consumers are predicted to preferentially eat food with a composition similar to their own bodies (Elser et al, 2000). A similar result was found in an experiment with fish where rudd and grass carp consistently preferred animal prey over plant food, both in short-term feeding trials at 18°C and in 10-week pond experiments with water temperatures varying from 16 to 24°C (Dorenbosch & Bakker, 2011. Even though the omnivores showed a consistent strong preference for animal prey, they did consume plant material in the choice trial at all temperatures where both food types were presented ad libitum.…”
Section: Discussionsupporting
confidence: 68%
“…Whereas our modelling results are supporting the hypothesis, it remains to be tested under field conditions. Macrophyte nutrient concentrations increase upon fertilization and are more preferred food under experimental conditions for omnivorous ducks and fish (Dorenbosch & Bakker, 2011;Bakker & Nolet, 2014), but in the field, the relation between environmental and macrophyte nutrient concentrations is less clear (e.g. Casey & Downing, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophytes differ in their efficiency to retain nutrients (Engelhardt & Ritchie, 2001), in their suitability as substrate for macrofauna (McAbendroth et al, 2005;Declerck et al, 2011) and in their importance as food for herbivores (Dorenbosch & Bakker, 2011). Several studies have reported enhanced water clarity above charophyte vegetation (Scheffer et al, 1994;Hargeby et al, 2007), although this clearing effect is not limited to charophytes (Kosten et al, 2009b).…”
Section: The Role Of Macrophyte Species In Ecosystem Stabilitymentioning
confidence: 99%